Antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid as well as preparation method and application of antibacterial finishing agent
By combining with quaternary ammonium chitosan and tannin on PET fabrics through hydrogen bonding, the problem of insufficient adhesion of existing antibacterial finishing agents on polyester fabrics is solved, and efficient and simple antibacterial loading and excellent antibacterial properties are achieved.
Patent Information
- Application Number
- CN202411869528.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing CS antibacterial finishing agents have insufficient adhesion on surface-inert fabrics such as polyester, resulting in cumbersome preparation process and high cost.
The antibacterial coating was prepared by hydrogen bonding of polyethylene terephthalate (PET) fabric with quaternary ammonium salt chitosan (QACS) and tannin (TA), which was simplified into a one-step impregnation-drying process.
An efficient antibacterial load is achieved, the preparation process is simplified, the cost is reduced, and the antibacterial performance is improved.
Smart Images

Figure CN119593208A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial materials, and in particular to an antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid, a preparation method and application thereof. Background Art
[0002] Chitosan (CS) is a natural polymer that can be extracted in large quantities from the shells of marine animals (Advances in Polymer Science; Springer, 2021; pp. 131–168); one of its derivatives is quaternary ammonium chitosan (QACS), which has good water solubility and antibacterial properties. The quaternary ammonium salt groups on the QACS molecular chain have strong electrostatic interactions with the bacterial membrane, which can destroy the bacterial membrane (Carbohydr Polym 2023, 312, 120796), thereby killing bacteria. If QACS is blended with other antibacterial agents to form a composite antibacterial agent, its antibacterial properties will be enhanced. Tannic acid (TA) is a small molecule with antibacterial properties that can kill bacteria by interacting with membrane proteins through hydrogen bonds (J Biomater Appl 2022, 36, 1503–1523). Jiao et al. prepared an antibacterial hydrogel containing QACS and TA (Carbohydr Polym 2022, 286, 119314). The antibacterial activity of hydrogels containing QACS and TA is better than that of hydrogels containing only QACS. This inspired us to prepare QACS and TA two-component coatings on fabrics to obtain better antibacterial properties. Fouilloux et al. prepared QACS and TA cross-linked coatings on polypropylene (PP) fabrics (ACS Applied Bio Material 2023, 6, 5609–5620). They first sprayed CS on the surface of PP fabric; then immersed it in oxidized TA solution, and cross-linked CS with oxidized TA through Schiff base reaction; finally, quaternary ammonium salt was grafted onto CS. The preparation of QACS and TA cross-linked coatings requires three steps, which are cumbersome and costly.
[0003] The antibacterial components of existing CS antibacterial finishing agents have weak adhesion to fabrics with inert surfaces such as polyester. In order to improve adhesion, researchers often use methods such as plasma pretreatment (Journal of Cleaner Production 2016, 118, 187-196) and multi-step cross-linking reactions (ACS Applied Bio Material 2023, 6, 5609–5620), and the process flow is relatively cumbersome. If the formula is optimized and polyhydroxy TA is introduced to enhance the hydrogen bonding between CS and polyester, it is expected to simplify the preparation process of antibacterial fabrics. Summary of the invention
[0004] In order to solve the problems existing in the background technology, the purpose of the present invention is to provide an antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid, a preparation method and application. The present invention uses polyethylene terephthalate (PET) fabric instead of PP fabric, so PET can be combined with QACS and TA through hydrogen bonds, and an antibacterial coating can be prepared on the fabric surface without cross-linking, and QACS and TA are used as antibacterial finishing agents, and antibacterial polyester fabric can be prepared by one-step dipping-drying.
[0005] The technical solution of the present invention is as follows:
[0006] 1. An antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid:
[0007] It is mainly a mixed solution containing quaternary ammonium salt chitosan, tannic acid and glacial acetic acid;
[0008] The solvent of the mixed solution is deionized water, the mass fraction of quaternary ammonium salt chitosan in the mixed solution is 0.1% to 3%, the mass fraction of tannic acid is 0.1% to 3%, and the volume fraction of glacial acetic acid is 0.5% to 2%.
[0009] 2. A method for preparing an antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid, the method comprising the following steps:
[0010] S1, dispersing chitosan in deionized water, stirring until dissolved, obtaining a chitosan solution, then adding 2,3-epoxypropyltrimethylammonium chloride (GTMAC) to the chitosan solution, heating and stirring, reacting for a period of time, purifying and drying, obtaining quaternary ammonium salt chitosan (QACS);
[0011] S2, dissolving glacial acetic acid in deionized water to obtain an acetic acid solution, then adding the quaternary ammonium salt chitosan described in step S1 to the acetic acid solution and stirring until it is clear and transparent, then adding tannic acid (TA) and stirring to obtain a mixed solution as an antibacterial finishing agent.
[0012] In the step S1, the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:0.32-2.9, that is, the molar ratio of amino groups in chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:0.33-3;
[0013] More preferably, the mass of chitosan is 6.0 g to 7.0 g, the mass of 2,3-epoxypropyltrimethylammonium chloride is 6.0 to 7.0 g, the volume of deionized water is 260 mL, the deacetylation degree of chitosan is about 97%, the heating temperature is 80 to 90° C., and the reaction time is 12 to 24 hours.
[0014] In the step S1, purification is to dialyze the solution after the reaction, and drying is to add the purified solution to a rotary evaporator to evaporate and remove the solvent to obtain a residue, and then the residue is dried under vacuum conditions at 40° C. to constant weight.
[0015] In step S1, the chemical preparation process of the reaction is as follows;
[0016]
[0017] The dialysate used in the dialysis is deionized water. The dialysis time is 5 to 9 days, and 5 L of the dialysate is replaced every day.
[0018] 3. Application of an antibacterial finishing agent in fabric antibacterial treatment.
[0019] 4. A method for improving the antibacterial properties of fabrics with an antibacterial finishing agent, the method comprising:
[0020] The fabric is immersed in the antibacterial finishing agent, then taken out from the antibacterial finishing agent, immersed in deionized water for washing to remove the antibacterial agent that is not firmly bound, and finally the fabric is taken out from the deionized water for drying to a constant weight.
[0021] Preferably, the mass ratio of the fabric to the antibacterial finishing agent is 1:100-1:200; the mass ratio of the fabric to deionized water is 1:600-1:700; the washing time does not exceed 10 minutes, the drying temperature is 50-70°C, and an electric blast oven is used. The fabric is, for example, polyester fabric.
[0022] Compared with the background technology, the present invention has the following beneficial effects:
[0023] The preparation process of the antibacterial finishing agent is simple and fabrics with high antibacterial agent loading can be obtained through one-step impregnation-drying. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 For CS and QACS 1 H-NMR spectrum.
[0025] Figure 2 This is a graph showing the relationship between the weight gain of fabric after finishing and modification and the QACS content in the finishing agent.
[0026] Figure 3 SEM images of the fabric before and after modification.
[0027] In the figure: (a) PET, (b) PET@TA, (c) PET@QACS / TA-0.1%, (d) PET@QACS / TA-0.3%, (e) PET@QACS / TA-2%, (f) PET@QACS.
[0028] Figure 4 This is a picture of the counting plate for the antibacterial test of fabrics.
[0029] Among them, (a) bacterial solution blank control, (b) untreated and modified polyester fabric, and (c) treated and modified polyester fabric PET@QACS / TA-2%.
[0030] Figure 5 This is the antibacterial test results of the modified fabric PET@QACS / TA-2%.
[0031] In the figure: * indicates that PET did not show antibacterial activity against E. coli in the experiment; the error bar at ** is 0, that is, all PET@QACS / TA-2% showed 100% antibacterial activity against S. aureus. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the method provided by the present invention is described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0033] The embodiments of the present invention are as follows:
[0034] Embodiment 1:
[0035] Add chitosan (6.4470g, 40mmol amino group) to 260mL deionized water and stir to evenly disperse the chitosan. Add GTMAC (6.1856g, 40mmol) and stir to react at 85°C for 16 hours. The reaction mixture was dialyzed with deionized water for 7 days, and the deionized water (5L) was replaced once a day. The solvent was evaporated and removed in a rotary evaporator. The residue was vacuum dried at 40°C to constant weight to obtain quaternary ammonium chitosan. The quaternary ammonium chitosan (about 10mg) was dissolved in a mixed solvent of heavy water (0.55mL) and deuterated trifluoroacetic acid (0.040mL) to prepare a nuclear magnetic resonance sample. Figure 1 As shown, the comparison between QACS and CS 1 According to the H-NMR spectrum and calculated by formula 1, the quaternary ammonium salt grafting ratio (DQ) of QACS is 16%.
[0036]
[0037] Among them, I 11 It is from QACS 1 The integrated area of H11 in the H-NMR spectrum, I 3-6 It is from QACS 1 The integrated area of H3-H6 in the H-NMR spectrum.
[0038] Prepare 4.5 mL of 1% (volume fraction) acetic acid solution, then add 0.0055 g of quaternary ammonium chitosan and 0.1234 g of tannic acid, stir until the solution is clear and transparent, and obtain an antibacterial finishing agent. Cut the polyester fabric into 2 cm × 2 cm samples (about 30 mg). Immerse the sample in the antibacterial finishing agent and then take it out immediately. Finally, dry the sample at 60 ° C to constant weight. The sum of the mass fractions of quaternary ammonium chitosan and tannic acid in the antibacterial finishing agent is 3%, of which the mass fraction of quaternary ammonium chitosan is 0.1% and the mass fraction of tannic acid is 2.9%. According to the mass fraction of quaternary ammonium chitosan in the antibacterial finishing agent, the finished and modified polyester fabric is named PET@QACS / TA-0.1%.
[0039] Embodiment 2:
[0040] Quaternary ammonium chitosan was obtained by the same method as in Example 1. 4.5 mL of 1% (volume fraction) acetic acid solution was prepared, and then 0.0157 g of quaternary ammonium chitosan and 0.1143 g of tannic acid were added, and stirred until the solution was clear and transparent to obtain an antibacterial finishing agent. The sum of the mass fractions of quaternary ammonium chitosan and tannic acid in the antibacterial finishing agent was 3%, of which the mass fraction of quaternary ammonium chitosan was 0.3% and the mass fraction of tannic acid was 2.7%. The polyester fabric was cut into 2 cm × 2 cm samples (about 30 mg). The sample was immersed in the antibacterial finishing agent and then immediately taken out. Finally, the sample was dried at 60 ° C to constant weight. According to the mass fraction of quaternary ammonium chitosan in the antibacterial finishing agent, the finished and modified polyester fabric obtained was named PET@QACS / TA-0.3%.
[0041] Embodiment 3:
[0042] Quaternary ammonium chitosan was obtained by the same method as in Example 1. 4.5 mL of 1% (volume fraction) acetic acid solution was prepared, and then 0.1032 g of quaternary ammonium chitosan and 0.0260 g of tannic acid were added, and stirred until the solution was clear and transparent to obtain an antibacterial finishing agent. The sum of the mass fractions of quaternary ammonium chitosan and tannic acid in the antibacterial finishing agent was 3%, of which the mass fraction of quaternary ammonium chitosan was 2% and the mass fraction of tannic acid was 1%. The polyester fabric was cut into 2 cm × 2 cm samples (about 30 mg). The sample was immersed in the antibacterial finishing agent and then immediately taken out. Finally, the sample was dried at 60°C to constant weight. According to the mass fraction of quaternary ammonium chitosan in the antibacterial finishing agent, the finished and modified polyester fabric obtained was named PET@QACS / TA-2%.
[0043] The weight gain of the modified fabric is calculated by formula 2:
[0044] weight gain=(m 1 -m 0 ) / m0 ×100% (2)
[0045] Among them, m 0 is the mass of fabric before modification, m 1 The quality of fabric after finishing modification.
[0046] Compared with Example 1 and Example 2, the weight gain of the fabric PET@QACS / TA-2% obtained after finishing and modification in Example 3 is 15% (e.g. Figure 2 ), and the surface load of antimicrobial agents is the highest (as shown in Figure 3 This indicates that the antibacterial finishing agent in Example 3 has the strongest binding force with the polyester fabric and is the optimal formula.
[0047] The antibacterial test of the sample was carried out according to GB / T 20944.2-2007 "Evaluation of antibacterial properties of textiles Part 2: Absorption method". The test bacteria were Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus). The finished and modified fabric was cut into 1cm×1cm size and inoculated with 10 5 CFU / mL bacterial solution 10μL. After static culture in a 37℃ constant temperature incubator for 24h, add 1mL PBS and vortex for 2min to elute the bacteria, take 0.1mL of the eluate to plate, and culture the plate at 37℃ for 24h.
[0048] The pure bacterial solution was used as the blank control group, and the antibacterial rate was calculated by formula (3):
[0049]
[0050] Among them, x represents the number of colonies on the counting plate of the pure bacterial solution group, and y represents the number of colonies on the counting plate of the experimental group.
[0051] Antibacterial test results Figure 4 and Figure 5 As shown, the test results show that the antibacterial activity of PET@QACS / TA-2% against E. coli is 99.2%, and the antibacterial activity against S. aureus is 100%, which is much higher than that of unmodified polyester fabric.
[0052] Comparative Example 1:
[0053] Prepare 4.5 mL of 1% (volume fraction) acetic acid solution, then add 0.1290 g of tannic acid and stir until the solution is clear and transparent to obtain an antibacterial finishing agent. The mass fraction of tannic acid in the antibacterial finishing agent is 1%. Cut the polyester fabric into 2 cm × 2 cm samples (about 30 mg). Immerse the sample in the antibacterial finishing agent and then take it out immediately. Finally, dry the sample at 60 ° C to constant weight. The finished and modified polyester fabric is named PET@TA.
[0054] Compared with Example 3, Figure 2 As shown, the loading amount of the antibacterial agent in the fabric PET@TA obtained in Comparative Example 1 is small, less than 1%; under electron microscope observation, the results are as follows Figure 3 As shown, there is almost no antimicrobial loading on the PET@TA surface.
[0055] Comparative Example 2:
[0056] The quaternary ammonium salt chitosan was synthesized as in Example 1. 4.5 mL of 1% (volume fraction) acetic acid solution was prepared, and then 0.1292 g of quaternary ammonium salt chitosan was added and stirred until the solution was clear and transparent to obtain an antibacterial finishing agent. The mass fraction of quaternary ammonium salt chitosan in the antibacterial finishing agent was 1%. The polyester fabric was cut into 2 cm × 2 cm samples (about 30 mg). The sample was immersed in the antibacterial finishing agent and then immediately taken out. Finally, the sample was dried at 60°C to constant weight. The finished and modified polyester fabric obtained was named PET@QACS.
[0057] Compared with Example 3, Figure 2 As shown, the loading amount of the antibacterial agent in the fabric PET@QACS obtained in Comparative Example 2 is small, less than 8%; under electron microscope observation, the results are as follows Figure 3 As shown, the antimicrobial agent loading on the PET@TA surface is less.
[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and modifications without departing from the method of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid, characterized in that: It is mainly a mixed solution containing quaternary ammonium salt chitosan, tannic acid and glacial acetic acid.
2. The antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid according to claim 1, characterized in that: The solvent of the mixed solution is deionized water, the mass fraction of quaternary ammonium salt chitosan in the mixed solution is 0.1%-3%, the mass fraction of tannic acid is 0.1%-3%, and the volume fraction of glacial acetic acid is 0.5%-2%.
3. The method for preparing the antibacterial finishing agent containing quaternary ammonium salt chitosan and tannic acid according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: S1, dispersing chitosan in deionized water, stirring until dissolved, obtaining a chitosan solution, then adding 2,3-epoxypropyltrimethylammonium chloride to the chitosan solution, heating and stirring, reacting for a period of time, purifying and drying, and obtaining quaternary ammonium salt chitosan; S2, dissolving glacial acetic acid in deionized water to obtain an acetic acid solution, then adding the quaternary ammonium salt chitosan described in step S1 to the acetic acid solution and stirring, then adding tannic acid and stirring to obtain a mixed solution as an antibacterial finishing agent.
4. The preparation method according to claim 3, characterized in that: In the step S1, the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:0.32-2.9, that is, the molar ratio of amino groups in chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:0.33-3, the heating temperature is 80-90°C, and the reaction time is 12-24 hours.
5. The preparation method according to claim 3, characterized in that: In the step S1, purification is to dialyze the solution after the reaction, and drying is to evaporate the purified solution to obtain a residue, and then the residue is dried under vacuum conditions at 40° C. to a constant weight.
6. The preparation method according to claim 3, characterized in that: In step S1, the chemical preparation process of the reaction is as follows; 7. The preparation method according to claim 5, characterized in that: The dialysate used in the dialysis is deionized water, and the dialysis time is 5 to 9 days.
8. Use of the antibacterial finishing agent according to any one of claims 1 to 2 or the antibacterial finishing agent prepared by the preparation method according to any one of claims 3 to 7 in antibacterial fabrics.
9. A method for improving the antibacterial properties of fabrics by using the antibacterial finishing agent according to any one of claims 1 to 2 or the antibacterial finishing agent prepared by the preparation method according to any one of claims 3 to 7, characterized in that: The method comprises the following steps: immersing the fabric in the antibacterial finishing agent, then taking the fabric out of the antibacterial finishing agent, immersing the fabric in deionized water for washing, and finally taking the fabric out of the deionized water for drying to a constant weight.
10. The method according to claim 9, characterized in that: The mass ratio of the fabric to the antibacterial finishing agent is 1:100-1:200; the mass ratio of the fabric to deionized water is 1:600-1:700; the washing time does not exceed 10 minutes, and the drying temperature is 50-70°C.
Citation Information
Patent Citations
Chitosan quaternary ammonium salt antibacterial agent and preparation method thereof
CN116711725A
Cited By
Antibacterial chitosan modified polypropylene fiber and preparation method thereof
CN119465431A
Preparation method of antibacterial and antiviral degradable bacterial grass fiber blended yarn material
CN122649241A